Demand Response Potential of Detached Houses in Finnish Building Stock for Integration of Variable Renewable Power Generation and Reserve Power Limitation - Ilkka Jokinen; Matti Lehtonen; Juha Jokisalo; Janne Hirvonen; Risto Kosonen (IEEE Access)
With a rapid increase in variable renewable electricity generation such as wind power and solar photovoltaics, a power system must simultaneously incorporate flexible resources to maintain power balance. Detached houses, covering 34% of the Finnish built floor area, can be considered to include a thermal storage within their structure and indoor air due to their thermal inertia. In addition, a domestic hot water tank may be operated such that part of it is utilized as a thermal storage. Moreover, since a large part of the detached houses utilize electricity as an energy source for their heating, either directly (28%) or indirectly with heat pumps (15%), these buildings may be utilized as demand response units within the power system. Thus, this study analyzed how the demand response of detached houses in Finland can increase the utilization of variable renewable power generation while mitigating the required reserve power capacity and energy in the power system. Furthermore, the effect of different wind and solar power generation capacities was analyzed together with several scenarios for the Finnish building stock. It was found that during the analyzed six-year period, the demand response was able to lower the required additional power source capacity significantly by 0.44 to 0.62 GW (10.0-13.1%) and the energy reasonably, 1.41 to 2.23 TWh (2.5–11.6%) by increasing the utilization of renewables. Noting that the high shares of energy reductions were due to very high share of renewables. These reductions corresponded to emission reductions of 0.51 to 0.80 Mt-CO2 (1.1–2.4%).